2022
DOI: 10.1055/s-0042-1755460
|View full text |Cite
|
Sign up to set email alerts
|

Iron Salts, High Levels of Hemoglobin and Ferritin in Pregnancy, and Development of Gestational Diabetes: A Systematic Review

Abstract: Objective The aim of this study was to systematically review literature on the use of iron supplements (not including iron derived from diet), increased levels of hemoglobin and/or ferritin, and the risk of developing gestational diabetes mellitus (GDM). Data source The following databases were searched, from the study's inception to April 2021: PUBMED, Cochrane, Web of Science, Scopus, Embase, Cinahl and Lilacs. Selection of studies A total of 6,956 titles and abstracts were reviewed, 9 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 38 publications
0
0
0
1
Order By: Relevance
“…Diante disso, a análise das conclusões dos trabalhos para a compreensão dos atuais estudos sobre a temática. Diante da análise dos trabalhos selecionados, pode-se compreender que a associação entre suplementação de ferro e DMG não é correlacionado, a partir de uma da utilização, na década de 2000, da suplementação de ferro para mulheres com níveis adequados de hemoglobina e ferritina sérica, como forma profilática de anemia gestacional, levantando a hipótese de maior risco para o desenvolvimento de DMG (Miranda, 2023). O DMG pode ser caracterizado como um grave problema de saúde mundialmente, caracterizado por aproximadamente 25%, de acordo com a Sociedade Brasileira de Diabetes.…”
Section: Resultsunclassified
“…Diante disso, a análise das conclusões dos trabalhos para a compreensão dos atuais estudos sobre a temática. Diante da análise dos trabalhos selecionados, pode-se compreender que a associação entre suplementação de ferro e DMG não é correlacionado, a partir de uma da utilização, na década de 2000, da suplementação de ferro para mulheres com níveis adequados de hemoglobina e ferritina sérica, como forma profilática de anemia gestacional, levantando a hipótese de maior risco para o desenvolvimento de DMG (Miranda, 2023). O DMG pode ser caracterizado como um grave problema de saúde mundialmente, caracterizado por aproximadamente 25%, de acordo com a Sociedade Brasileira de Diabetes.…”
Section: Resultsunclassified
“…Several PC studies have indicated an association between SF concentrations or dietary intake of haem iron/dietary patterns rich in sources of haem iron and the risk of developing GDM (Durrani et al., 2021 ; Fernandez‐Cao et al., 2017 ; Fu et al., 2016 ; Iqbal & Ekmekcioglu, 2019 ; Kataria et al., 2018 ; Miranda et al., 2022 ; Parlesak et al., 2024 ; Petry, 2022 ; Yang et al., 2022 ; Zhao et al., 2017 ).…”
Section: Assessmentmentioning
confidence: 99%
“…Eligible outcomes were measures of incidence of GDM and measures of glucose homeostasis. Pertinent studies were retrieved based on the searches performed for the systematic review by the contractor (Parlesak et al, 2024) and by manual searching the reference lists of available systematic and narrative reviews (Durrani et al, 2021;Fernandez-Cao et al, 2017;Fu et al, 2016;Iqbal & Ekmekcioglu, 2019;Kataria et al, 2018;Miranda et al, 2022;Petry, 2022;Yang et al, 2022;Zhao et al, 2017).…”
Section: Gestational Diabetes Mellitusmentioning
confidence: 99%